Perancangan Sistem Informasi Berbasis Web pada Puskesmas Sirah Pulau Padang - Dedi Haryanto; Muhammad Ikhsan Saputra; Muhammad Ihsan (Teknik Komputer Politeknik Negeri Sriwijaya, 2022)
The Community Health Center is one of the health service organizations that always strives to achieve efficiency and effectiveness of services to the community, so it takes a supporting facility for processing website-based information system data that can provide information quickly and accurately, but the Sirah Pulau Padang Public Health Center is in the process of processing information systems that provide accurate information. in Sirah Pulau Padang Health Center, they still use the manual method by using paper as a processing tool so that various problems eventually emerge. Such as the difficulty of controlling user data information, poly data, patient data and patient visit data, inventory of information caused by human error, the process of finding patient data becomes long and less accurate due to the accumulation of paper containing data, and due to the nature of paper that is easily damaged, it is very possible for data loss to occur. The formulation of the problem in this study is the risk of inaccurate data caused by human error in the data recording process, the risk of data loss caused by the nature of paper that is easily damaged, and the slow data search process. This study used qualitative research methods. So the author made a website to support the performance of the Padang Island Sirah Health Center, based on the results of research conducted at the Sirah Pulau Padang Health Center with the title Web-Based Information System Design at the Padang Island Sirah Health Center, it can be concluded that this study succeeded in creating an information system using the website method.